Cultural and Folkloric Reflections in Advertising - Yağmur Dalar (Uluslararası Halkbilimi Araştırmaları Dergisi)
Advertisements are powerful means of communication that reflect the effects of culture on social structures and bear the traces of folk culture. Beyond just being the elements that shape consumption habits, these are areas where cultural identities are reflected, social memory is strengthened, and traditional values are integrated into modern society. Television and digital advertising in Turkey combine elements and cultural symbols of folk culture with modern marketing strategies to shape social perception and strengthen cultural identities. In particular, the presence of elements based on folk culture in the language of advertising provides important traces that show how traditional culture is transformed through modern media and how it is associated with the cultural memory of the people. The universe of the study is created by advertisements published in Turkey and the sample is created by advertisements containing folkloric elements of folk culture. Six television commercials published in the last fifteen years have been determined by judicial sampling and these advertisements have been examined using qualitative content analysis and semantic analysis methods. In line with the analysis, a holistic evaluation method was adopted and it was discussed how folkloric elements were tried to be transferred to folk culture through advertisements. While the findings of the study reveal how folk culture and folklore are reflected in advertisements, they also reveal how ads based on folk culture transform the cultural structure of societies and social perception. In particular, advertisements blend folkloric elements with modern consumer culture, reshaping social identities and reinforcing cultural memory. This process reveals the interaction between the dynamic nature of public culture and the evolution of digital media and advertising. Thus, the power of advertising plays a critical role in keeping folk culture alive, reproducing and transforming social structures.